Effect of Standardized IV Compounding Protocols on Patient Safety Outcomes (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Intravenous (IV) medications are classified as high-risk therapies due to their direct entry into the systemic circulation and limited opportunity for error correction. Errors during IV compounding may result in severe adverse drug events, infections, increased healthcare costs, and patient morbidity. This study examines the effect of implementing standardized IV compounding protocols on patient safety outcomes in hospital pharmacy IV rooms. A structured review of international guidelines and published studies was conducted, complemented by analysis of reported safety indicators such as medication errors, contamination rates, and adverse drug events. Findings demonstrate that standardized protocols significantly reduce compounding errors, improve aseptic compliance, and enhance overall patient safety. The study highlights the importance of protocol-driven IV room practices aligned with USP , ISMP, ASHP, and accreditation standards.